2011
DOI: 10.1103/physrevb.84.075129
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Hall effects in a Weyl semimetal: Possible application in pyrochlore iridates

Abstract: There have been lots of interest in pyrochlore Iridates A2Ir2O7 where both strong spin-orbital coupling and strong correlation are present. A recent LDA calculation 1 suggests that the system is likely in a novel three dimensional topological semi-metallic phase: a Weyl semi-metal. Such a system has zero carrier density and arrives at the quantum limit even in a weak magnetic field. In this paper we discuss two novel quantum effects of this system in a magnetic field: a pressure-induced anomalous Hall effect a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
604
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 846 publications
(624 citation statements)
references
References 33 publications
(50 reference statements)
5
604
1
Order By: Relevance
“…More recently, the research on topological states has been extended to three-dimensional (3D) semimetal systems. [8][9][10][11][12] These systems could demonstrate many fascinating phenomena, such as Weyl fermion quantum transport and various Hall effects, [13][14][15][16] consequently become the rising stars of the field. Up to now, three kinds of topological semimetals have been discovered, i.e., 3D Dirac semimetal (DSM), 12,[17][18][19][20][21] Weyl semimetal (WSM), 8,9,22,23 and node-line semimetal (NLS).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the research on topological states has been extended to three-dimensional (3D) semimetal systems. [8][9][10][11][12] These systems could demonstrate many fascinating phenomena, such as Weyl fermion quantum transport and various Hall effects, [13][14][15][16] consequently become the rising stars of the field. Up to now, three kinds of topological semimetals have been discovered, i.e., 3D Dirac semimetal (DSM), 12,[17][18][19][20][21] Weyl semimetal (WSM), 8,9,22,23 and node-line semimetal (NLS).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been an increased interest in the study of 5d transition metal oxides where these energy scales are all comparable. Iridium based oxides such as the square-lattice materials (Sr,Ba) 2 IrO 4 1-3 , the perovskites SrIrO 3 and Sr 3 Ir 2 IO 7 4 , the pyrochlore materials A 2 Ir 2 O 7 (A = Y,Eu,Lu,Sm) [5][6][7] , the honeycomb-lattice materials A 2 IrO 3 (A = Na,Li) [8][9][10] , and the hyperkagome-lattice material Na 4 Ir 3 O 8 11,12 have been materials of intensive recent investigations. The 5d transition metal oxides are expected to be wide-band weakly correlated metals due to large spatial extent of their d-orbitals.…”
Section: Introductionmentioning
confidence: 99%
“…According to the recent theoretical studies of the lattice Hamiltonian, 23,25,26 it is shown that when the quadratic-SM is the non-magnetic ground state, the local Coulomb interaction can give rise to the AIAO type magnetic ground state, 2π , where 2k 0 is the distance between two WPs. 14,28,29 To understand the relation between the AHE and the distribution of WPs, it is convenient to introduce a Chern vector C = (C x , C y , C z ), which is defined as…”
Section: D Bulk Propertiesmentioning
confidence: 99%
“…For example, the Hall conductivity of a Weyl-SM having only a pair of WPs at ±k 0 = (0, 0, ±k 0 ) is given by σ xy = e 2 h 2k 0 2π , where 2k 0 is the distance between two WPs. 14,28,29 To understand the relation between the AHE and the distribution of WPs, it is convenient to introduce a Chern vector C = (C x , C y , C z ), which is defined as…”
Section: D Bulk Propertiesmentioning
confidence: 99%
See 1 more Smart Citation